IRAN-AFGHANISTAN BORDER MANAGEMENT AND MIGRATION CHALLENGES: A COMPREHENSIVE ANALYSIS - Niaz Mohammad Hamdard; Mohammad Jamal Shinwari; Irfan Ullah Stanikzai (International Journal of Contemporary Issues in Social Sciences, 2024)
Aim: The aim of this study is to conduct a comprehensive analysis of Iran-Afghanistan border management and migration challenges. Methods: The research methodology involved content analysis to identify key themes and patterns, followed by framework analysis. Non-probability sampling was used to obtain in-depth insights, and relevant news articles, research articles, and books were selected based on relevance and credibility. Results: The results indicate that Iran plans to establish a joint free trade center with Afghanistan, facilitates visas for Afghan traders and workers to prevent illegal migration, shares historical and cultural bonds, implements security measures at the border, announces plans to block parts of the border, and engages in coordination efforts to resolve border problems and ensure smooth cross-border movement. Conclusion: In conclusion, the analysis reveals the importance of collaborative economic integration, border facilitation, historical and cultural bonds, while also highlighting the need for balanced border security measures and coordinated efforts to address border challenges. Recommendation: Foster economic integration, enhance border facilitation, strengthen cultural bonds, balance border security measures, promote bilateral coordination, seek mutual understanding on border closure, and emphasize regional security cooperation.